small differentiated carcinomas of the thyroid - Delgado, Bolívar; Risi, Leonardo (Cirugía del Uruguay, 1992)
The authors make a revision of this subject as regards a series of 26 operated patients with sma/1 differentiated carcinomas of the tyroid (less than 15 mm). They point out these tumors' main features: they are frequently occult, of incidental finding, and with excel/ent prognosis when treated by means of a lees-than-total thyroidectomy